non-human person - Perez Pereda, Beatriz (Cinzontle, 2025)
Beatriz Pérez Pereda was born in Tabasco, Mexico in 1983. She is the Carlos Pellicer Ibero-American Fine Arts Poetry Prize for published work 2023, the Carmen Alardín National Poetry Prize 2022, the Óscar Oliva Poetry Prize 2022, the Dolores Castro Poetry Prize 2021, among others. His most recent books are Chronicles towards Pluto (ITAC, 2022) and Persona no humano (CONARTE, 2022). He teaches reading and writing workshops, interviews authors for the cultural supplement La Gualdra. He studied literary creation and law.